A Decision Support Tool for VTS Centers to Detect Grounding Candidates (Transport Systems and Processes, 2011)
Some factors that could affect the shape and size of a domain useful for grounding scenarios are ship main characteristics (length, breadth, draft, speed, and type), her maneuverability, navigator experience and his familiarity to the area, shape and depth of the waterway, engine and rudder characteristics, and weather condition; which some of them are not easy to consider and to model. In addition, the 3rd dimension (depth) is vital for defining the ship domain for grounding since the grounding is defined as the event that the bottom of a ship hits the seabed, in compare with stranding, which is defined as theA. Mazaheri, F. Goerlandt, J. Montewka* & P. Kujala Aalto University School of Engineering, Espoo, Finland * Aalto University School of Engineering, Espoo, Finland, Maritime University of Szczecin, PolandABSTRACT: AIS (Automatic Identification System) data analysis is used to define ship domain for grounding scenarios. The domain has been divided into two areas as inner and outer domains. Inner domain has clear border, which is based on ship dynamic characteristics. Violation of inner domain makes the grounding accident unavoidable. Outer domain area is defined with AIS data analyzing. Outer domain shows the situation of own ship in compare with other similar ships that previously were in the same situation. The domain can be used as a decision support tool in VTS (Vessel Traffic Service) centers to detect grounding candidate vessels. In the case study presented in this paper, one type of ship, which is tanker, in a waterway to Sköldvik in the Gulf of Finland is taken into account.